PENGARUH SUASANA KELAS TERHADAP HASIL BELAJAR PPKn SISWA KELAS VIII SMP IT AZIZIYYAH PEKANBARU - Rini, Rini; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was conducted and motivated by problems that arise from interviews conducted by researchers in SMP IT Aziziyyah Pekanbaru who have poor learning outcomes. The school has made various rules or rules along with an evaluation of ways of teaching students to give and cultivate a sense of wanting to learn from within students. The purpose of this study to know about the influence of classroom atmosphere on the results of learning PPKn students class VIII SMP IT Aziziyyah Pekanbaru. This research method using quantitative descriptive analysis, the data in the analysis by using simple linear regression method. Based on the results of this study it can be concluded that the recapitulation of respondents' answers questionnaire about the effect of classroom atmosphere on the learning outcomes of PPKn students of grade VIII SMP IT Aziziyyah Pekanbaru is for the recapitulation of respondent classroom atmosphere (X) which answer very agree with percentage 30.271% and 40.141 % and for the less agree of 21.451%, and the disagreeing of 7,868%. Based on this research in category good enough where in Test R² can be seen that contribution of influence of Class Atmosphere to result of Learning of SMP IT Aziziyyah Pekanbaru is equal to 22,5%. While the rest is influenced by other variables that are not included in this study.Keywords: Class Suffering, Learning Outcomes